The death of Cleopatra - Retief, Francois P.; Cilliers, Louise (Acta Theologica, 2005)
The last days and death of Cleopatra and Mark Antony are reviewed. Antony died a slow death after an initially unsuccessful suicide attempt by way of a stab wound to the abdomen. It is argued that Cleopatra (and her two servants) probably committed suicide through poisoning, rather than the bite of an asp (viper) as is popularly believed. Death occurred very rapidly and the bodies showed no recognisable snake bite wounds. Fatal viper bites are characteristically associated with prominent, swollen and haemorrhagic wounds. Cobras may cause rapid death in spite of minor bite wounds, but in order to kill three adults, the snake would have to be large. Legend has it that the reptile was smuggled to Cleopatra in a small basket of figs, which would not have been possible with a large snake.